Tradition of Saprahan as a Learning Resource for Civic Education in the Era of Globalization to develop Citizenship Skills - Tri Utami; Sulistyarini Sulistyarini (STKIP Singkawang, 2025)
This study aims to determine how the Saprahan tradition in Sepinggan Gelik Sambas Regency can be a learning resource for Citizenship Education and can develop citizenship skills. The type of research used in this research was qualitative research. The data collection techniques used in this research was interviews, observation and documentation. The values contained in the Saprahan tradition was he values of mutual cooperation, unity, simplicity, and religion. The values contained in the Saprahan tradition can be an effective learning resource in civic education. Integration of Saprahan values in learning can build active community participation in social life.